The valve motion characteristics of a reciprocating pump. (January 2016) - Pei, Junfeng; He, Chao; Lv, Miaorong; Huang, Xianru; Shen, Kejun; Bi, Kunlei
Abstract: In previous studies on a reciprocating pump, the state, behavior simulation, or experimental analysis of the valve was seldom reported. In the paper, taking a triplex single-acting reciprocating pump as the research object, we established an experimental system for testing valve disc׳s motion parameters to directly acquire the valve disc motion parameters (acceleration, velocity, and displacement) under actual conditions. Moreover, testing results were compared with the calculation results obtained according to U. Adolph Theory and Approximation Theory. In Approximation Theory, the valve disc motion was not fully considered, thus leading to the large deviation from the actual situation. Compared with the Approximation Theory, U. Adolph Theory is more suitable for the determination of valve disc motion parameters during different strokes and can explain the jumping and hysteresis phenomena of the valve well. A new pump testing method and an experimental system were proposed to provide a new study approach for valve design theory, disc damage mechanism, and pump failure diagnosis. Highlights: Sensor installation on the valve disc in a pressurized liquid was settled. A experimental system for testing valve disc׳s motion parameters was established. The U. Adolph and Approximation Theory has been confirmed experimentally.